A High Resolution Melting Analysis (HRM) PCR assay for the detection and identification of Old World Leishmania species - Saadi-Ben Aoun, Yusr; Souguir, Hejer; Chouaieb, Hamed; Kraiem, Mongia; Bel Hadj Ali, Insaf; Chakroun, Ahmed S.; Noguier, Florian; Fathallah-Mili, Akila; Piquemal, David; Guizani, Ikram (PLOS Neglected Tropical Diseases, 2024)
Author summary Cutaneous Leishmaniases (CL) are a group of diseases considered as the most Neglected Tropical Diseases. CL present a complex epidemiology situation in many countries over the World and particularly in Africa and Middle East regions with the proven implication of different Leishmania species causing pleomorphic clinical presentations. Migrations, climate change and variations, agricultural developments are factors complicating eco-epidemiology and driving emerging trends. Leishmania species identification is pivotal for etiological diagnosis and patients’ management, and to establish adequate control measures. Molecular techniques are the most accurate methods for detection and identification of Leishmania parasites due to their higher sensitivity and specificity. HRM PCR assay constitutes a valuable test for rapid and reliable diagnosis of infectious diseases including CL. The present study aimed at the development of an HRM PCR targeting the Strumpellin gene, which would be useful for accurate CL diagnosis by detecting and identifying causal Leishmania parasites. Bioinformatic analyses explored conserved regions flanking interspecific polymorphisms to select HRM PCR target fragment and primer pairs and develop the assay. We confirmed through this study the relevance of this target and of our new method for CL diagnosis by proving the principle of using it to simultaneously detect and identify Leishmania parasites in human samples, thereby its potential to improve CL-patient management, surveillance and control in well-equipped health centers.